The Flow Behavior of Organic Liquids Inside Carbon Nanotubes - Barilka, A.G.; Balabai, R.M. (Physics and Chemistry of Solid State, 2016)
Within the methods of electron density functional and ab initio pseudopotential, it were obtained the spatial distributions of density of valence and the total energy for migration of water (or methanol) inside carbon nanotubes with clean walls and lined inside with gold atoms. It was found that the mass transfer of methanol through the carbon nanotubes of the zigzag type (15,0) is two orders of magnitude more energy than water.. It was revealed that the mass transfer of water and methanol through carbon nanotubes covered with gold atoms on the inner sides requires an order of magnitude more energy than pure nanotubes.